Prediction of the Therapeutic Effects of Pembrolizumab and Nivolumab in Advanced Non-Small Cell Lung Cancer by Platelet-Derived Microparticles in Circulating Blood. (19th February 2021) - Liu, Tingting; Wang, Jiang; Liu, Yanxin; Wu, Jionghe; Yuan, Yaping; Wang, Chao; Fang, Xiangqun; Li, Hongxia
Background: There are limited methods to predict the therapeutic effect of immune checkpoint inhibitors (ICIs). The purpose of this study was to explore the value of circulating microparticles (MPs) in predicting thetherapeutic effects of immunotherapy. Methods: A prospective study was conducted at the cancer center of PLA general hospital, including all patients with advanced non-small cell lung cancer (NSCLC) who were treated with pembrolizumab or nivolumab from December 2018 to December 2019. The patients were divided into an immune-related objective response (iOR) group and an immune-related disease progression (iPD) group.The numbers of total MPs, platelet-derived microparticles (PMPs) and T-lymphocyte-derived microparticles (T-LyMPs) at baseline and after immunotherapy were detected using a flow cytometer. Univariate analysis and multivariate logistic regression analysis were used to determine the independent influencing factors. Results: We identified 32 patients in the iOR group and 18 patients in the iPD group. No significant difference were found intotal MPs, PMPs and T-LyMPs at the baseline between the 2 groups. While total MPs, PMPs and T-LyMPs in the iPD group were significantly higher than those in the iOR group after immunotherapy(P < 0.05). In the multivariate logistic regression analysis, PMPs ≥80 events/µL after immunotherapy(OR, 7.270; 95% CI, 1.092-48.404, P = 0.04) were associated with disease progression in advanced NSCLC and could independently predict the therapeutic effect of immunotherapy. Conclusions: PMPs after immunotherapy independently predicted the therapeutic effects of ICIs, making it possible to monitor the therapeutic effect in real time and rapidly adjust treatment regimens. In addition, this study found for the first time that elevated circulating T-LyMPs were associated with disease progression in advanced NSCLC.